Analisis Hasil Belajar Praktik Pembuatan Kemeja dengan Teknik Ban Berjalan pada Mata Pelajaran Desain Produksi Busana di Kelas XI Busana SMK Negeri 3 Payakumbuh - Zelasmi, Reza; Puspaneli, Puspaneli (TSAQOFAH, 2025)
This study examines the learning outcomes of Grade XI Fashion students at SMK Negeri 3 Payakumbuh in shirt-making practice using the assembly line technique and individual practice. The main problem is the lack of students’ comprehensive understanding of the entire shirt-making process, as the assembly line technique assigns each group to work on only certain stages. The study used a quantitative method with a sample of 57 students from a population of 132. The independent variable was the assembly line technique, while the dependent variable was practical learning outcomes. Data were obtained from practical assessment scores and individual test results based on the fashion production design module rubric. The results show that 100% of students achieved mastery in the assembly line practice, while only 60% achieved mastery in individual practice. A moderate and significant correlation was found between the learning outcomes of the assembly line technique and individual practice (r_calculated = 0.410 > r_table = 0.2162; significance 10%). In conclusion, the assembly line technique effectively improves practical learning outcomes in shirt-making and has a significant effect on individual learning outcomes; however, additional guidance is still needed to ensure students understand the entire shirt-making process.